2021
DOI: 10.1108/ijse-08-2020-0588
|View full text |Cite
|
Sign up to set email alerts
|

Demographic dividend and economic growth in emerging economies: fresh evidence from the SAARC countries

Abstract: PurposeThe study attempts to establish the relationship between demographic dividend and GDP growth rate by utilising panel data from 1990 to 2017 in Bangladesh, India, Pakistan, Nepal and Sri Lanka.Design/methodology/approachThis study employs the pooled OLS model, using data from the World Bank's database for the period 1990–2017 for five selected South Asia Association for Regional Cooperation (SAARC) countries.FindingsThe results reveal that demographic dividend affects economic growth in Bangladesh, India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…But women arguably have less access to these opportunities because of many social norms and a lack of education and skills. Jafrin et al (2021) observe demographic dividend impacted the economic growth of the five SAARC countries but this economic growth is unaffected by trade openness and unemployment rates in these countries. The authors find that the rate of labor force participation is negatively related to the GDP growth rate in the aggregated model in the SAARC countries.…”
Section: Saarc and Sadc: Income-based Classificationmentioning
confidence: 90%
“…But women arguably have less access to these opportunities because of many social norms and a lack of education and skills. Jafrin et al (2021) observe demographic dividend impacted the economic growth of the five SAARC countries but this economic growth is unaffected by trade openness and unemployment rates in these countries. The authors find that the rate of labor force participation is negatively related to the GDP growth rate in the aggregated model in the SAARC countries.…”
Section: Saarc and Sadc: Income-based Classificationmentioning
confidence: 90%
“…Using data from a SAARC nation panel between 1990 and 2017 for Bangladesh, India, Pakistan, Nepal, and Sri Lanka, Jafrin et al (2021) evaluate the link between demographic dividend and economic growth. Their findings also support prior research in the South Asian setting, which found that demographic dividend boosts economic growth.…”
Section: Theme 1: Age Structure Demographic Dividend and Economic Gro...mentioning
confidence: 99%
“…Can we see here an opportunity for developing countries and countries in transition, which have a high birth rate? This question was treated by several authors such as Jafrin et al (2021) who highlighted that appropriate policies need to be defined and adopted in order to strengthen the considerable benefits of demographic dividend on economic growth; the workforce is at least almost utilized.…”
Section: Introductionmentioning
confidence: 99%